OTENTISITAS HADIS MENUTUP TELINGA SAAT MENDENGARKAN MUSIK - Sulhadi, Asep; Sholihah, Izzatus (SAMAWAT: Journal Of Hadith and Qur'anic Studies, 2022)
Some time ago, there was a video on social media that showed a group of students waiting in line in a room when they were about to take part in the COVID-19 vaccination activity, then all of them closed their ears and lowered their heads because they heard western music playing in the queue room.Pros and cons also occurred with many people providing comments, ranging from ustadz, boarding school caregivers, lecturers, high-ranking Indonesian Ulema Council officials, members of the council, musicians and even artists who did not miss commenting on the incident.Those who are pro or support the above incident, quote a narration from one of the Tabi'in, namely Nafi' Maula Ibn Umar who said that Ibn Umar once saw the Messenger of Allah cover his ears when listening to music or rather when he heard the sound of a shepherd's flute.In this article the author wants to test the authenticity of the history with the aim of knowing whether the hadith is authentic and valid so that it can be used as evidence and a source of law or vice versa.Keywords: music, hadith, otentic